Superiority of bivalirudin over heparin anticoagulation therapy for extracorporeal membrane oxygenation? Too early to draw conclusions. Issue 2 (February 2023) - Gu, Jie; Yu, Hongjie; Lin, Dang
Abstract: Background: We aimed to compare the efficacy and safety of bivalirudin versus heparin as the anticoagulant in patients undergoing extracorporeal membrane oxygenation (ECMO). Methods: We conducted a search in PubMed, Embase and the Cochrane Library for all the studies in which bivalirudin was compared to heparin as the anticoagulant for ECMO. Efficacy outcomes were defined as the time to reach therapeutic levels, time within therapeutic range (TTR), thrombotic events, circuit thrombosis, circuit exchanges. Safety outcomes were reported as heparin-induced thrombocytopenia (HIT), major bleeding events, minor bleeding events. Other outcomes included hospital length of stay (LOS), ICU LOS, mortality, 30-day mortality and in-hospital mortality. Results: Ten studies with 1091 patients were included for meta-analysis. A significant reduction in thrombotic events [OR 0.51, 95%CI 0.36, 0.73, p  = 0.0002, I 2  = 0%], major bleeding events [OR 0.31, 95%CI 0.10, 0.92, p  = 0.04, I 2  = 75%] and in-hospital mortality [OR 0.63, 95%CI 0.44, 0.89, p  = 0.009, I 2  = 0%] treated with bivalirudin were found compared with heparin. There were no significant differences between groups regarding the time to reach therapeutic levels [MD 3.53, 95%CI −4.02, 11.09, p  = 0.36, I 2  = 49%], TTR [MD 8.64, 95%CI −1.72, 18.65, p  = 0.10, I 2  = 77%], circuit exchanges [OR 0.92, 95%CI 0.27, 3.12, p  = 0.90, I 2  = 38%], HIT [OR 0.25, 95%CI 0.02, 2.52, p  = 0.24, I 2  = 0%], minor bleeding events [OR 0.93, 95%CI 0.38, 2.29, p  = 0.87, I 2  = 0%], hospital LOS [MD −2.93, 95%CI -9.01, 3.15, p  = 0.34, I 2  = 45%], ICU LOS [MD −4.22, 95%CI -10.07, 1.62, p  = 0.16, I 2  = 0%], mortality [OR 1.84, 95%CI 0.58, 5.85, p  = 0.30, I 2  = 60%] and 30-day mortality [OR 0.75, 95%CI 0.38, 1.48, p  = 0.41, I 2  = 0%]. Conclusion: Bivalirudin probably be a potential choice for ECMO anticoagulation. However, based on the included studies' limitation, the superiority of bivalirudin over heparin for anticoagulation in the ECMO population still require further prospective randomized controlled studies before a definite conclusion.